2014
DOI: 10.1186/1746-6148-10-132
|View full text |Cite
|
Sign up to set email alerts
|

Observed management practices in relation to the risk of infection with paratuberculosis and to the spread of Mycobacterium avium subsp. paratuberculosisin Swiss dairy and beef herds

Abstract: BackgroundMany studies have been conducted to define risk factors for the transmission of bovine paratuberculosis, mostly in countries with large herds. Little is known about the epidemiology in infected Swiss herds and risk factors important for transmission in smaller herds. Therefore, the presence of known factors which might favor the spread of paratuberculosis and could be related to the prevalence at animal level of fecal shedding of Mycobacterium avium subsp. paratuberculosis were assessed in 17 infecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 30 publications
2
24
0
Order By: Relevance
“…A higher proportion of individuals in the coinfected group also belonged to herds where calves were fed with colostrum from multiple cows and also with waste milk. This is not surprising since the main MAP transmission route in ruminants is oral, by ingestion of food or water contaminated with feces from infected animals, including ingestion of the bacterium from contaminated pastures (Doré et al 2012;Künzler et al 2014). Furthermore, in a study of subclinically infected cows, MAP shedding in colostrum (22.2 % of cows) was 3 times higher than in milk (8.3 %) (Streeter et al 1995), indicating the importance of discarded milk (colostrum and milk) as a way of transmission.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A higher proportion of individuals in the coinfected group also belonged to herds where calves were fed with colostrum from multiple cows and also with waste milk. This is not surprising since the main MAP transmission route in ruminants is oral, by ingestion of food or water contaminated with feces from infected animals, including ingestion of the bacterium from contaminated pastures (Doré et al 2012;Künzler et al 2014). Furthermore, in a study of subclinically infected cows, MAP shedding in colostrum (22.2 % of cows) was 3 times higher than in milk (8.3 %) (Streeter et al 1995), indicating the importance of discarded milk (colostrum and milk) as a way of transmission.…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that husbandry practices could allow the entrance of some infectious agents into a herd or the transmission among other animal population groups (Diéguez et al 2008;Humblet et al 2009;Kennedy et al 2014;Künzler et al 2014). The negative impact of both mycobacteria species on animal and public health, and given its complicated infection biology, seems to be important issues to be addressed.…”
Section: Introductionmentioning
confidence: 97%
“…Although MAP was only proven in the faeces of two animals, Bayesian estimates of true prevalence indicated that 20% [95% confidence interval (CI) 3 -38] of herds had at least one MAP-positive cow with a within-herd prevalence of positive herds of 22% (95% CI 8-42). In a Swiss study, a within-herd prevalence of 6•4% in seven infected beef herds was detected by faecal culture and PCR in pools of three [20]. The number of animals sampled in these herds ranged from 25 to 130 with an average number of 56 animals aged >1 year.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we expected to find a higher proportion of MAP-positive animals (by ELISA, as well as, by fecal culture and PCR) in the study herd, considering inappropriate herd management practices present and known to be risk factors for the disease (e.g. presence of animals born at other dairies, exposure of calves 0-6 weeks to adults feces, feces spread on forage fed to any age group (Collins et al, 1994;Goodger et al, 1996;Jakobsen et al, 2000;Wells and Wagner, 2000;Diéguez et al, 2008;Tiwari et al, 2009;Sorge et al, 2012;Künzler et al, 2014;Fernández-Silva and Ramírez-Vásquez, 2015;Vilar et al, 2015). When a test combination is considered, it must be taken into account that some infected cows produce antibodies for several years prior to the fecal-shedding of detectable quantities of MAP.…”
Section: Discussionmentioning
confidence: 99%